2007
DOI: 10.1007/s00125-007-0893-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of progression from impaired fasting glucose and impaired glucose tolerance to diabetes in a high-risk screened population: 3 year follow-up in the ADDITION study, Denmark

Abstract: Aims/hypothesis We sought to identify determinants of progression from impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) to diabetes in high-risk screened individuals. Methods In general practices in Denmark, stepwise screening for type 2 diabetes mellitus in persons aged 40 to 69 years included a risk questionnaire, random blood glucose, HbA 1c , fasting blood glucose and an OGTT. The 1,821 individuals with IGT or isolated IFG (WHO 1999) were re-invited after 1 and 3 years. Follow-up data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 36 publications
8
61
0
4
Order By: Relevance
“…These conclusions need to be seen in context. Several previous studies have reported on the predictive role of fasting or post-load glucose levels for incident type 2 diabetes, but the two have rarely been assessed together and after controlling for other strong predictors (age, BMI and familial diabetes) [4,5]. The present analysis shows that an equivalent (i.e.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…These conclusions need to be seen in context. Several previous studies have reported on the predictive role of fasting or post-load glucose levels for incident type 2 diabetes, but the two have rarely been assessed together and after controlling for other strong predictors (age, BMI and familial diabetes) [4,5]. The present analysis shows that an equivalent (i.e.…”
Section: Discussionmentioning
confidence: 47%
“…Criteria for lesser degrees of dysglycaemia are less well established. Impaired glucose tolerance (IGT), defined by the 2 h glucose concentration, carries heightened risk of diabetes [3][4][5] and, possibly, cardiovascular disease [6][7]. The pathophysiology of IGT is a combination of insulin resistance, hepatic as well as peripheral, and beta cell dysfunction [8] that is similar to that of diabetes, only of a milder degree.…”
mentioning
confidence: 99%
“…Setting and population The study population was drawn from the Danish arm (DK) of the Anglo-Danish-Dutch Study of Intensive Treatment in People with ScreenDetected Diabetes in Primary Care (ADDITION), which evaluated a systematic screening for people at high risk of type 2 diabetes conducted among all listed patients aged 40 to 69 years in the 175 participating Danish practices [9]. Blood samples collected at baseline screening (2001 to 2006) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples collected at baseline screening (2001 to 2006) were used. Details on the original ADDITION recruitment strategy can be found elsewhere [9]. Of the people who completed the risk score questionnaire (n=134,016, response rate 82%), those who had a high risk score (n= 28,041) underwent a step-wise clinical assessment comprising the following: determination of random blood glucose and HbA 1c , and measurement of fasting blood glucose and an OGTT.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, weight loss can slow or halt the pathogenesis of type 2 diabetes. When a group of individuals with impaired glucose tolerance was followed over time, weight loss of only 1 kg decreased the incidence of diabetes by 20% [43].…”
Section: Assembling the Time-course To Type 2 Diabetesmentioning
confidence: 99%